Implementation of Educational Curriculum Through the Keep Learning Approach to Improve the Quality of Education at SMPN Mesjid Raya: A Literature Study - Suryati Suryati; Rahmattullah Rahmattullah; Siti Mayang Sari (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
This study examines the implementation of the educational curriculum in SMPN Mesjid Raya through the "Keep Learning" approach, aimed at enhancing the quality of education. The "Keep Learning" approach emphasizes continuous learning, adaptability, and engagement among both educators and students. This research adopts a literature study methodology, analyzing various scholarly sources related to curriculum development and quality education. The findings reveal that the "Keep Learning" approach fosters a dynamic learning environment, encourages critical thinking, and supports lifelong learning habits in students. Furthermore, the study highlights the importance of teacher training, resource availability, and community involvement in successfully implementing this approach. It concludes that integrating the "Keep Learning" philosophy into the curriculum can significantly contribute to improved educational outcomes in SMPN Mesjid Raya.